The Effectof Organizational Climate and Compensation on Employee Job Satisfaction in The Social Service of Gorontalo District - Junita Claudia Pahrun; Hapsawati Taan; Amrain Mustafa (Journal of Economic, Business, and Administration (JEBA), 2020)
The objectives of this study are: 1) to examine the influence of organizational climate on job satisfaction of the employees of the Gorontalo District Social Service; 2) to examine the effect of compensation on job satisfaction of Gorontalo District Social Service staff; 3) to test the effect of organizational climate and compensation simultaneously on job satisfaction of employees of the Gorontalo District Social Service. This study uses a descriptive research approach and explanatory research methods. Explanatory method is research that proves the existence of cause and effect and a relationship that affects or is influenced by two or more variables under study. Research quantitative research which is based on the philosophy of positivism, is used to examine specific populations or samples, data collection using research instruments, quantitative/statistical data analysis, with the aim of testing predetermined hypotheses. The research was conducted at the Gorontalo District Social Service and was carried out from August to December 2020 with a total sample of 51 people. Based on the results of data processing, the conclusions are formulated, namely: 1) there is a positive and real influence of organizational climate on employee job satisfaction at the Gorontalo District Social Service, which means that the higher the organizational climate, the higher the employee job satisfaction; 2) there is a positive and real effect of compensation on job satisfaction of employees at the Gorontalo District Social Service, which means that the better the compensation, the higher the job satisfaction of the employees; 3) there is a positive and real influence simultaneously between organizational climate and compensation on employee job satisfaction at the Gorontalo District Social Service. This means that the higher the organizational climate and the better the compensation, the higher the employee's job satisfaction.